The Effect of Peer Group Education on Smoking Behavior in Youth in Student Vocational School Taman Siswa Padang 2018 - Nurleny, Nurleny (LPPM Universitas Prima Nusantara Bukittinggi, 2018)
ABSTRACT WHO (2008), put Indonesia 4.8% as the country with the third highest number of smokers in the world after China as much as 30% and India as much as 11.2%. Smokers in Indonesia on average start smoking at the age of 15-19 years, which at age is the age of adolescents. One effort to provide information about the dangers of smoking in adolescents is through peers ( peer group). The purpose of this study is to determine the effect of Peer Group Education on smoking behavior in adolescents at SMK TAMAN SISWA Padang in 2018. The research type is pre-experiment with One-Group Pre-Test-Post-Test approach implemented in SMK Taman Siswa Padang in December 2017 until May 2018. The population is class X and class XI total of 60 people where class X there are 25 students and class XI 35 student at SMP Taman Siswa Padang with sample amounted to 24 students. Univariate data analysis with frequency distribution and bivariate analysis with paired sample t-test with a confidence level of 95%. Â Results showed average knowledge teenager before getting peer group education intervention was 6.21, after getting peer group education intervention was 14.54, average adolescent attitude before getting peer group education intervention is 34.88, after getting peer group education intervention was 52.25, the average teenage action before getting peer group education intervention was 3.33 and after obtaining peer group education intervention was 8.12 . It can be concluded differences in knowledge, attitude and practice about smoking before and after getting peer group education intervention. Suggestion for school parties needs to work with local health agencies to conduct cooperation in the form of health education to students, especially about the dangers of smoking for students.Â